Implementasi Advanced Encryption Standard 128 Sebagai Pengamanan Basis Data Obat-obatan Apotek - Yudi Wiharto; Mufti Mufti (Maranatha University Press, 2022)
Confidentiality and data security are two important things in data communication as an effort to maintain the confidentiality and security of data, so this study aims to create a system that is used to increase the confidentiality and security of drug data at pharmacies by using Advanced Encryption Standard 128, where the algorithm cryptography Advanced Encryption Standard (AES-128) as the method to be used. Encryption testing is done by doing a comparison between manual calculations and the results of encryption on the system, besides that Blackbox testing is also carried out. Making this system is done by collecting data, designing a system with a database. The result of making the system is a webbased application that is used in the activities of pharmacists or pharmacy employees to input and manage drug data.